The Effect of Participatory Leadership Style and Organizational Culture on Employee Performance : JEL Classification: M12, M14, D23, L32 - Nadia, Nadia; Kusdarianto, Indra; Wahida, Altri (Journal La Bisecoman, 2025)
In the current research, the authors conduct research aimed at determining the determinants of performance among the employees in government institutions; however, they argue that employee performance cannot be attributed to factors/determinants like managerial initiative alone but the collective influence of the leadership behaviour and the institutional culture combined. The empirical study, with quantitative research design and a sample of 50 employees taken as a random sample of Perumda Tirta Mangkaluku, Palopo City, uses multiple regressions in statistically examining the correlation between participative leadership, organisational culture and performance. This result shows that there is a positive relationship between participative leadership and performance but a point must be made that this effect is significantly weaker compared to that of organisational culture. In particular, participative leadership contributes only 27.9 percent of the variance in performance yet organisational culture contributes 59.6 percent. The findings give the impression that performance is not only dependent on the managerial efforts but is inherent in the organisation itself in terms of normative architecture. Culture, unlike appearing as a peripheral variable, is utilized as a constitutive power that influences behaviour among employees. The research, therefore, highlights the importance of programming not only to leadership training or institutional process reform, but to the development of meaning systems, symbolic integration and cultural conformity that would make high performance accessible and sustainable.